Nurses' Knowledge and Skills regarding Oxygen Administration Methods at Pediatric Teaching Hospitals in Mosul City - Ahmed, Mohammed; Radha, Afifa (Iraqi National Journal of Nursing Specialties, 2020)
Objective: To assess knowledge and skills level regarding oxygen administration methods at pediatric teaching hospitals in Mosul City.Methodology: A descriptive study was applied at pediatric teaching hospitals (Al-Kansaa, and Ibn Al-Atheer) in Mosul City from 8 of October / 2018 till 29 of May / 2019. The selection of the sample was non- probability (Purposive). This sample involved of (52) nurses. The questionnaire was constructed which consists of three parts and provided for nurses. The questionnaire validity was carried out through a panel of experts. To evaluate statistically the reliability of instruments, the pilot study was applied through period from 20– till –31 of January / 2019. Non-randomly (6) nurses from Ibn Sina teaching hospitals, the correlation of Pearson's coefficient result are (r= 0.798) and are significant at p ≤ 0.05 level was used to approximation the scale (test – retest) by using SPSS version 25. The Result show statistical knowledge and skills results for nurse's in concerning the oxygen administration methods for pediatric, that knowledge results are 84.6% (44) of them at not acceptable level, and the skills results are 65.4 % (34) of them also at not acceptable level. There are not significant relationships between the knowledge, skills results and all the demographic variables except the skills results with training courses only there are significant relationships at p≤ 0.05.Recommendations: Training course and workshops for nurses of teaching hospitals regarding oxygen administration methods